Research on developing sustainable and climate-resilient livelihood in Giao An commune, Giao Thuy district, Nam Dinh province - Nguyễn, Hoài Thu (2020)
The current situation of livelihoodsinGiao An commune are assessed. The climate variation in past, present and future in the research site are identified; The impacts of CC onlivelihoods intheresearch site are assessed; The resilience to CC of Giao An commune is investigated; The solutions todevelop sustainable and climate-resilient livelihoods for Giao An commune are proposed